Pelestarian warisan budaya Indonesia: Menjaga identitas di era modern - Wulandari, Aida Olivia Desy Tri (Maliki Interdisciplinary Journal, 2024)
This article describes the importance and challenges of maintaining Indonesia’s cultural heritage amidst the dynamics of the modern era. Indonesia’s rich and diverse cultural heritage is a marker of national identity that plays a central role in maintaining the nation’s historical roots. This article examines the positive impact of maintaining cultural heritage on a sense of identity, the creative economy and tourism. However, such maintenance is faced with various challenges, including declining interest from younger generations and threats to historic sites by urbanization and climate change. Measures such as public education, government support, and utilization of modern technology are described as solutions to safeguard Indonesia’s precious cultural heritage. This article invites us to jointly care for and celebrate this cultural wealth in order to strengthen national identity in an era that continues to develop.